2017
DOI: 10.1007/s10015-017-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of biped walking posture by dynamical-evaluating index

Abstract: In this paper, biped walking posture and design are evaluated through dynamic reconfiguration manipulability shape index (DRMSI). DRMSI is the concept derived from dynamic manipulability and reconfiguration manipulability with remaining redundancy. DRMSI represents the ability of dynamical system of manipulators possessing shape changing acceleration in task space by normalized torque inputs, while the hand motion is assigned as the primary task. Besides, we use visual lifting approach to stabilize the walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was suggested that in studying the kinematics and dynamics of bipeds, locomotion and manipulation should be considered without separation because similarities seem to exist between these functions. Some studies have used the concept of manipulability in a dynamic level [2,17,22,33]. Center of mass (CoM) manipulability and zero moment point (ZMP) manipulability have also been studied in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that in studying the kinematics and dynamics of bipeds, locomotion and manipulation should be considered without separation because similarities seem to exist between these functions. Some studies have used the concept of manipulability in a dynamic level [2,17,22,33]. Center of mass (CoM) manipulability and zero moment point (ZMP) manipulability have also been studied in previous studies.…”
Section: Introductionmentioning
confidence: 99%